Anthropometric Evaluation of Nutritional Status of Adolescents Attending the Secondary Schools 1 and 2 of Gagnoa (Côte d'Ivoire) - Yao N’guessan Blaise; N’dia Kouadio Frédéric; Oussou N’guessan Jean-Baptiste; Yapo Angoué Paul (European Scientific Journal, ESJ, 2019)
This study aims to evaluate the nutritional status of adolescents attending two secondary schools in Gagnoa (Côte d'Ivoire) based on anthropometric parameters. A sample of 184 adolescents was recruited in the secondary schools 1 and 2 of Gagnoa. Measurements of body mass and height were made using a scale and a measuring board equipped with a tape measure respectively. Anthropometric indices (height-for-age Z-score and BMI-forage Z-score) were calculated according to the WHO (2007) growth references for 5-19 years old children. Mean age was 14.9 ± 0.2 years, mean body weight was 48.2 ± 0.7 kg and mean height was 156.1 ± 0.7 cm. The results of this study revealed a deficit of 13% and an underweight of 8.7%. Undernutrition in the population is characterized by 1.6% severe chronic undernutrition, 11.4% moderate chronic undernutrition, 8.7% moderate acute malnutrition and 0.5% severe acute malnutrition. The prevalence of obesity in this population was 0.5%. The assessment of the nutritional status of the adolescents attending the two secondary schools of Gagnoa has revealed deficiency stature and thinness among students.